Soluble receptor for advanced glycation end-products independently influences individual age-dependent increase of arterial stiffness - Gelžinský, Július; Mayer, Otto; Seidlerová, Jitka; Mateřánková, Markéta; Mareš, Štěpán; Kordíková, Veronika; Trefil, Ladislav; Cífková, Renata; Filipovský, Jan (Hypertension research, 2020)
Circulating levels of soluble receptor for advanced glycation end-products (sRAGE) have been suggested to have a protective role in neutralizing advanced glycation end-products (AGEs) and their pathological effects on vessel walls. We aimed to investigate the association between the circulating concentration of sRAGE and the dynamics of arterial wall stiffening as a manifestation of vascular aging in the general population. In a prospective cohort study, we longitudinally followed 530 general-population-based subjects (subsample of Czech post-MONICA study). Aortic pulse wave velocity (PWV) was measured twice (at baseline and after ~8 years of follow-up) using a SphygmoCor device (AtCor Medical Ltd), and the intraindividual change in PWV per year (∆PWV/year) was calculated. Concentrations of sRAGE were assessed at baseline by ELISA (R&D Systems). The average ∆PWV/year significantly decreased across the sRAGE quintiles (p = 0.048), and a drop by one sRAGE quintile was associated with an ~21% increase in the relative risk of accelerated age-dependent stiffening (∆PWV/year ≥ 0.2 m/s). Subjects in the bottom quintile of sRAGE (<889.74 pg/mL) had a fully adjusted odds ratio of accelerated stiffening of 1.72 (95% CI: 1.06-2.79), p = 0.028, while those with high sRAGE concentrations (≥1695.2 pg/mL) showed the opposite effect [odds ratio 0.55 (95% CI: 0.33-0.90), p = 0.017]. In conclusion, the circulating status of sRAGE independently influenced the individual progression of arterial stiffness over time. This finding strongly supports the hypothesis that high sRAGE has a protective role against vascular aging.
Keywords: dospělí; Receptor for Advanced Glycation End Products; Female; Pulse Wave Analysis; Age Factors; Adult; General population; ženské pohlaví; Aging; longitudinální studie; sRAGE; věkové faktory; lidé; analýza pulzové vlny; Prospective study; tuhost cévní stěny; krevní tlak; prospektivní studie; Male; Aged; Prospective Studies; stárnutí; Pulse wave velocity; lidé středního věku; senioři; mužské pohlaví; receptor pro konečné produkty pokročilé glykace; Vascular Stiffness; Vascular aging; Blood Pressure; AGEs; Middle Aged; Longitudinal Studies; Humans